Digital mammography with synchrotron radiation: characterization of a novel computed radiography system. (August 2015) - Trivellato, S; Vandenbroucke, D; Bessem, M; Fedon, C; Longo, R; Tromba, G; Taibi, A
Abstract: Breast X-ray imaging is a continuous research field to define dedicated equipment, with specialized X-ray sources and efficient detectors to improve image quality with an equal or even lower patient dose. The Needle Imaging Plate HM5.0, produced by Agfa, has been characterized using synchrotron radiation to assess the performance of this novel imaging chain in comparison to conventional mammographic equipment. The detection performance has been initially assessed in terms of Detective Quantum Efficiency (DQE) and its computation showed that DQE curves are very close to the typical results for digital radiography systems. Image threshold contrast has been then evaluated using the CDMAM phantom. The analysis has been completed with a scoring of visible details in the radiographs of the TORMAM phantom. The characterization thus confirms that monochromaticity leads to an equal image quality with a lower glandular dose and phase-contrast effects lead to an increase in anatomical structure detectability. Finally, a preliminary evaluation of clinical images showed a clear improvement in image quality thanks to phase-contrast contribution and to detector performance.